A kind of HIV-1 protease inhibitors containing phenols with antiviral activity against DRV-resistant variants. (15th June 2022) - Hu, Shangjiu; Ma, Ling; Dong, Biao; Shan, Qi; Zhou, Jinming; Zhang, Guoning; Wang, Minghua; Cen, Shan; Zhu, Mei; Wang, Juxian; Wang, Yucheng
Graphical abstract: Abstract: Based upon the preliminary design of enhancing genetic barrier to drug-resistant viral mutants by maximizing hydrogen-bonding or other van der Waals contacts, we have designed, synthesized and biologically evaluated a new class of HIV-1 protease inhibitors with phenol derived P 2 ligands and nitro or halogens in P 2′ ligands. Results indicate that a majority of inhibitors exhibit robust enzyme inhibitory with IC50 values in picomolar or single digit nanomolar ranges. Among which, compound 17d displays potency with IC50 value of 21 pM and high protease selectivity. Of note, 17d exhibits greater antiviral activity against the DRV-resistant variant than the efficacy against the wild type virus. Furthermore, the molecular modeling studies demonstrate important interactions between 17d and the active sites of both the wild-type and DRV-resistant HIV-1 protease, as well as furnish insights for further optimization of new inhibitors.